Micronised Egyptian blue pigment: A novel near-infrared luminescent fingerprint dusting powder - Errington, B.; Lawson, Glen; Lewis, Simon; Smith, G. (Elsevier, 2016)
In this paper we demonstrate that micronised Egyptian blue pigment can be used as a safe and simple material to visualise latent fingerprints on non-porous surfaces as near-infrared luminescent impressions. This allows the detection of latent fingerprints on highly patterned and reflective surfaces that have proven challenging with existing techniques.